Characterisation of pulmonary function trajectories: results from a Brazilian cohort. Issue 3 (25th August 2020) - Weber, Priscila; Menezes, Ana Maria Baptista; Gonçalves, Helen; Perez-Padilla, Rogelio; Jarvis, Deborah; de Oliveira, Paula Duarte; Wehrmeister, Fernando César
Background: Pulmonary function (PF) trajectories are determined by different exposures throughout the life course. The aim of this study was to investigate characteristics related to PF trajectories from 15 to 22 years in a Brazilian cohort. Methods: A birth cohort study (1993 Pelotas Birth Cohort) was conducted with spirometry at 15, 18 and 22 years. PF trajectories were built based on z-score of forced expiratory volume in 1 s (FEV1 ), forced vital capacity (FVC) and their ratio using a group-based trajectory model. Associations with exposures reported from perinatal to 22 years were described. Results: Three trajectories, low (LT), average (AT) and high (HT) were identified in 2917 individuals. Wealthiest individuals belonged to the HT of FEV1 (p=0.023). Lower maternal pregestational body mass index (BMI) (22.4±0.2; p<0.001 and 22.1±0.14; p<0.001) and lower birth weight (3164.8±25.4; p=0.029 and 3132.3±19.4; p=0.005) were related to the LT of FEV1 and FVC. Mother's smoking exposure during pregnancy (37.7%; p=0.002), active smoking at ages 18 and 22 years (20.1% and 25.8%; p<0.001) and family history of asthma (44.8%; p<0.001) were related to the LT of FEV1 /FVC. Wheezing, asthma and hospitalisations due to respiratory diseases in childhood were related to the LT of both FEV1 and FEV1 /FVC. Higher BMIs were related to the HT of FEV1 and FVC at all ages. Conclusions: PF trajectories were mainly related to income, pregestational BMI, birth weight, hospitalisation due to respiratory diseases in childhood, participant's BMI, report of wheezing, medical diagnosis and family history of asthma, gestational exposure to tobacco and current smoking status in adolescence and young adult age. In this study, three pulmonary function trajectories were observed from adolescence to early adulthood. The trajectories tracked over the years of follow-up and were characterised by several exposures from the gestational period until 22 years of age. https://bit.ly/2XMc4J4